Web based car information system / Gowri Arumainthan - Gowri , Arumainthan (2004)
In today's world, the World Wide Web (www) has so much of information available on the Internet especially in the field of education. The internet allows the public to use the global market space to promote their products through a barrier that breaks all time, distance and place within which the Electronic Commerce can conduct itself. 'The Web Based Car Information System' is an e-commerce site that sells and promotes both new and used cars, providing maintenance tips, browsing and search facilities. That main objective of this project is to develop attractive, interactive and user friendly online selling website using FrontPage 2000.The development of the 'Web Based Car Information System; is emphasized to be a browser and platform independent. This will be accomplished by using Vb Script and Java Applet to code the client side processing while Active Server pages (ASP) to code the server side processing respectively. It is also aim to have a back-end database that is Microsoft Access 2000 for providing updates product information, user information and database. It is vital to develop the 'Web Based Car Information System' as it will be one of the few sites in Malaysia that will be selling and providing cars together with their maintenance online. This website will also provide complete information on cars to the buyer. This might boost opportunity for the user who wants to set up such a virtual store.